Royalism, print and censorship in revolutionary England - McElligott, Jason 1972- (Studies in early modern cultural, political and social history, 2007)
A study of the content and methods of royalist propaganda via newsbooks in the crucial period following the end of the first civil war. This is a study of a remarkable set of royalist newsbooks produced in conditions of strict secrecy in London during the late 1640s. It uses these flimsy, ephemeral sheets of paper to rethink the nature of both royalism and Civil War allegiance. Royalism, Print and Censorship in Revolutionary England moves beyond the simple and simplistic dichotomies of 'absolutism' versus 'constitutionalism'. In doing so, it offers a nuanced, innovative and exciting visionof a strangely neglected aspect of the Civil Wars. Print has always been seen as a radical, destabilizing force: an agent of social change and revolution. Royalism, Print and Censorship in Revolutionary England demonstrates, bycontrast, how lively, vibrant and exciting the use of print as an agent of conservatism could be. It seeks to rescue the history of polemic in 1640s and 1650s England from an undue preoccupation with the factional squabbles of leading politicians. In doing so, it offers a fundamental reappraisal of the theory and practice of censorship in early-modern England, and of the way in which we should approach the history of books and print-culture. JASON McELLIGOTT is the J.P.R. Lyell Research Fellow in the History of the Early Modern Printed Book at Merton College, Oxford